Relationship between Inequality and Poverty and the Impacts of Teachers and Schooling (International Journal of Innovative Research in Engineering & Management, 2022)
This study is a consequence of  dissatisfaction with the outcomes of recent educational  changes. These attempts failed. They must be given up. In  their place, we must acknowledge that economic disparity  creates numerous societal issues, including educational  issues. Sadly, among all affluent countries, the USA has  the greatest economic disparity between rich and poor.  There is a correlation between a country's or state's  economic imbalance and the prevalence of social  problems. As a result, better social and economic  initiatives might have a greater impact on our schools than  school curriculum alone. Teachers, curriculum,  assessment and administration have all been targeted as  potential causes of school failure. This article argues that  America's educational issues stem from factors outside of  school, mainly economic disparity. Thus, focused  economic and social policies may be more effective in  improving schools than virtually any other federal, state,  or municipal policy proposal. This article examines the  causes behind virtually every recent school reform effort's  failure. It is a study on how inequality impacts our society  as a whole, for example, research and social reforms that  may improve our educational establishments. The greatest  approach to improve American schools is to create  employment that pay a decent wage. Other programmes  for disadvantaged kids are mentioned. Inequality in  income, and the poverty that results from it, is what matters  most for education.
Keywords: Education; Entitlement; Inequality; PISA; Poverty